2022
DOI: 10.3389/fphys.2022.812237
|View full text |Cite
|
Sign up to set email alerts
|

Renal Function Recovery Strategies Following Marathon in Amateur Runners

Abstract: Long distance races have a physiological impact on runners. Up to now, studies analyzing these physiological repercussions have been mainly focused on muscle and cardiac damage, as well as on its recovery. Therefore, a limited number of studies have been done to explore acute kidney failure and recovery after performing extreme exercises. Here, we monitored renal function in 76 marathon finishers (14 females) from the day before participating in a marathon until 192 h after crossing the finish line (FL). Renal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…Of course also other transplant groups often suffer compromised kidney function [82][83][84]. A prospective study of 76 healthy marathon runners reported a 48% incidence of acute renal failure, mostly grade 1 [85]. Based on serum creatinine levels, earlier findings in 23 marathon runners indicated a 55% incidence of acute renal failure, while 74% of participants showed significant increases in tubular biomarkers [86].…”
Section: Renal Injurymentioning
confidence: 99%
“…Of course also other transplant groups often suffer compromised kidney function [82][83][84]. A prospective study of 76 healthy marathon runners reported a 48% incidence of acute renal failure, mostly grade 1 [85]. Based on serum creatinine levels, earlier findings in 23 marathon runners indicated a 55% incidence of acute renal failure, while 74% of participants showed significant increases in tubular biomarkers [86].…”
Section: Renal Injurymentioning
confidence: 99%